The universality of eAREs in animal feces suggesting that eAREs function possibly in horizontal gene transfer (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: This study aimed to pinpoint the universality of extracellular antimicrobial resistance elements (eAREs) and compare the contents of eAREs with those of intracellular AREs (iAREs) in animal feces, thus laying a foundation for the further analysis of the horizontal transfer of antimicrobial resistance genes (ARGs) in the animal guts. Materials and Methods: Extracellular DNAs were isolated from the fecal samples of Pavo cristatus (n = 18), Ursus thibetanus (n = 2), two breeds of broilers (n = 21 and 11, respectively), and from the contents of rabbit intestines (n = 5). eAREs were detected by PCR technology. iAREs in P. cristatus and broiler feces were also detected and compared with the corresponding eAREs. In addition, some gene cassettes of class 1 integrons were sequenced and analyzed. Results: The results showed that eAREs exist in animal feces and intestinal contents. In this study, different eAREs were detected from animal feces and intestinal contents, and tetA, tetB, sul1, sul2, class 1 integron, and IncFIB presented the highest detection rates. The detection rates of certain eAREs were significantly higher than those of parallel iAREs. The integral cassettes with intact structures were found in eAREs, and the cassettes carried ARGs. Conclusions: The presented study here sheds light on the presence of eAREs in animal feces or guts, and eAREs may play an important role in the horizontal gene transfer of ARGs. J. Adv. Vet. Anim. Res., 10(1): 103–112, March 2023http://doi.org/10.5455/javar.2023.j658